Hard projectile impact on layered SFRHSC composite target. (October 2015) - Wu, H.; Fang, Q.; Gong, Z.M.; Peng, Y.
Abstract: A series of hard projectile high-speed (500–700 m/s) impact tests on the steel fiber reinforced high strength concrete (SFRHSC) panel with rear steel liner and (or) backfilled sandy soil were conducted. The impact resistance of the above layered composite target as well as the parametric influences were assessed experimentally. It indicates that, within the discussed parameters variation ranges: (i) the rear sandy soil layer enhance the impact resistance of the SFRHSC/steel composite target; (ii) the steel liner also enhance the impact resistance of SFRHSC/sandy layer composite target; (iii) the strengthening effect of the rear sandy soil layer on the impact resistance of bare SFRHSC panel is more influential than the rear steel liner; (iv) Reinforcing steel bars of the concrete panel has no obvious effect on the impact resistance of SFRHSC/steel/sandy soil composite target; (v) Mixing steel fibers can efficiently reduce the damages of the concrete target. An approach for predicting the ballistic limits of SFRHSC/steel and SFRHSC/steel/sandy soil composite targets were proposed and compared with the present test data. Highlights: Projectile impact test on layered SFRHSC panel/steel liner/sandy soil target was conducted. The impact resistance of the composite target and the parametric influences were studied. Prediction models for ballistic limits of layered targets were proposed and validated.